Fasting plasma glucose levels are associated with all-cause and cancer mortality: A population-based retrospective cohort study. - Qing Gao; Qi Wang; Zhijuan Gan; Meng Wang; Dafeng Lu; Bingdong Zhan (PLoS ONE)
Despite a growing body of research indicating a link between fasting glucose levels and mortality, the relationship between fasting glucose and all-cause and cancer mortality remains inconsistent. In this study, we used Cox regression and restricted cubic spline models to analyze the association and dose-response relationship between fasting plasma glucose levels and all-cause and cancer mortality in a retrospective cohort based on data from the 2015 health check-ups of residents in Quzhou City. After a mean follow-up of 5.31 years for 148,755 study participants, 10,345 deaths occurred, with an all-cause mortality density of 131.09/10,000 person-years, of which 2,845 were cancer deaths, with a cancer mortality density of 36.05/10,000 person-years. There was a "J" shaped dose-response relationship between fasting plasma glucose levels and all-cause and cancer mortality. Relative to normal fasting glucose (NFG), the risk of all-cause mortality (HRs and 95% CIs) in the impaired fasting glucose (IFG) and diabetes mellitus (DM) groups was 1.11 (1.06, 1.16) and 1.43 (1.35, 1.52), respectively, and the risk of cancer mortality in the DM group was 1.22 (1.09, 1.37). In this cohort study, we found that fasting plasma glucose levels were significantly associated with the risk of all-cause and cancer mortality.